2023
DOI: 10.1212/wnl.0000000000206832
|View full text |Cite
|
Sign up to set email alerts
|

Child Neurology: Infantile Biotin Thiamine Responsive Basal Ganglia Disease

Abstract: Biotin thiamine responsive basal ganglia disease (BTRBGD) is an inherited autosomal recessive disorder that results from the inability of thiamine to cross the blood brain barrier.1-3It is considered a treatable condition if vitamin supplementation, most commonly with thiamine and biotin, is initiated early.2BTRBGD can present as an infantile form, classical childhood form, or adult Wernicke-like encephalopathy.3The infantile form is often the most severe and portends a worse prognosis with high mortality desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…All detected variants were inherited from asymptomatic parents that are heterozygous for the pathogenic variant. Figure 1 a is a schematic showing the location of all the SLC19A3 variants identified in this study on the six-exon gene structure, in addition to all SLC19A3 variants reported in the literature [ 6 , 12 , 17 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…All detected variants were inherited from asymptomatic parents that are heterozygous for the pathogenic variant. Figure 1 a is a schematic showing the location of all the SLC19A3 variants identified in this study on the six-exon gene structure, in addition to all SLC19A3 variants reported in the literature [ 6 , 12 , 17 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients with SLC19A3 deficiency usually have normal psychomotor development until the first episode of encephalopathy, which infections could trigger. The characteristics of BTRBGD are early onset encephalopathy, seizure, ataxia, bulbar dysfunction, and dystonia/hypotonia [ 20 ]. Brain MRI is abnormal in all symptomatic cases, and usually symmetrically distributed lesions could be seen, especially in caudate nuclei, putamen, and medial thalami.…”
Section: Discussionmentioning
confidence: 99%
“…Maney et al recently described a case of BTBGD diagnosed very early in a 2-month-old infant [ 8 ]. Our case emphasizes that BTBGD is a condition that can present with a milder, later-onset phenotype, further adding to the understanding of the disease spectrum.…”
Section: Discussionmentioning
confidence: 99%